CHEMICAL AND SENSORY CHARACTERISTICS OF ANALOGUE CHICKEN POPCORN BASED ON SHIITAKE MUSHROOMS, TVP, AND SEITAN - Jessica Lukito; Yuyun Yuniati; Adhania Andika Prayudanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Currently, plant-based foods are becoming a trend among the public, this is due to the increasing awareness of health and environmental sustainability. One potential innovation is analog popcorn chicken formulated from high-protein plant ingredients. This study aims to develop and analyze the characteristics of analog popcorn chicken based on shiitake mushrooms, TVP, and seitan as an alternative to meat. The study used a Completely Randomized Design (CRD) with four treatments in the form of variations in the concentration of the main ingredients. Chemical analysis included protein content, crude fiber, water content, and ash content, while organoleptic tests were carried out by 25 untrained panelists to assess color, aroma, taste, and texture. Chemical data were analyzed using ANOVA at a significance level of 5%, while sensory data were analyzed using the Kruskal–Wallis test. The results showed that variations in the proportion of ingredients had a significant effect (p<0.05) on water content, protein content, crude fiber content, and texture preferences, but did not significantly affect ash content, color, aroma, and taste. The best treatment was obtained in formulation A3 (25% shiitake and seitan mushroom mixture: 75% TVP) with chemical characteristics of 15.67% protein content, 9.32% crude fiber, 41.59% water content, and 3.24% ash content. Organoleptically, the best treatment product had a "like" acceptance level for all parameters with the highest texture preference score of 4.04. This product has the potential to be developed as a nutritious plant-based food alternative to processed meat.